Pengendalian Kualitas Crude Palm Oil Perusahaan Minyak Kelapa Sawit PT. Kalimantan Sanggar Pusaka Dalam Upaya Mengendalikan Tingkat Kerusakan Produk Menggunakan Alat Bantu Statistical Process Control - Noor, M Wildan; Fauziyah, Fauziyah (Jurnal Manajemen Bisnis, 2016)
This research aims to analyze the implementation of quality control product in order to improve product quality by using Statistical Process Control (SPC). Object in this research is theproduction process of Crude Palm Oil (CPO) from the procurement of raw materials to the end of the process and the subject is part of PT. Kalimantan Sanggar Pusaka. Data were analyzed using SPC such as control p-chart, control x-chart, Pareto charts and diagrams causation. Analysis of raw materials by using control-p chart showed that the quality control is still under control. Based on Pareto diagram analysis, the most dominant damage occurs because there are many pieces F0 / raw fruit (53%), based on analysis of cause-effect diagram this condition comes from many factors such as method, human, plant age, and cultivation techniques. Analysis production process of CPO in Oil Production by using control x-chart showed that the quality MOIST and DIRT are still out of the control limits. Based on Pareto diagram analysis, the most dominant damage occurs because the high levels of MOIST (39%), based on analysis of cause-effect diagram this condition comes from many factors such as methods, environment, raw materials, and machine. Analysis of the final product at the Storage Tank CPO by using map control-x showed that the quality MOIST and DIRT are still out of the control limits. Based on Paretodiagram analysis, the most dominant damage occurs because the high levels of DIRT and MOIST with respective percentages of 50%, based on the results of the analysis of cause-effect diagram this condition comes from many factors such as methods, environment, raw materials, and machine.